Starting and Operating a Public Cardiac Catheterization Laboratory in a Low Resource Setting: The Eight-Year Story of the Uganda Heart Institute Catheter Laboratory. Issue 1 (9th February 2021) - Rwebembera, Joselyn; Aliku, Twalib; Kayima, James; Lubega, Sulaiman; Sebatta, Elias; Kiggundu, Brian; Kirenzi, Daudi; Nyakoojo, Wilson; Mondo, Charles; Kumar, Krishna; Ratnayaka, Kanishka; Qureshi, Shakeel; et al.
Background: Low- and-middle-income-countries (LMICs) currently bear 80% of the world's cardiovascular disease (CVD) mortality burden. The same countries are underequipped to handle the disease burden due to critical shortage of resources. Functional cardiac catheterization laboratories (cath labs) are central in the diagnosis and management of CVDs. Yet, most LMICs, including Uganda, fall remarkably below the minimum recommended standards of cath lab:population ratio due to a host of factors including the start-up and recurring costs. Objectives: To review the performance, challenges and solutions employed, lessons learned, and projections for the future for a single cath lab that has been serving the Ugandan population of 40 million people in the past eight years. Methods: A retrospective review of the Uganda Heart Institute cath lab clinical database from 15 February 2012 to 31 December 2019 was performed. Results: In the initial two years, this cath lab was dependent on skills transfer camps by visiting expert teams, but currently, Ugandan resident specialists independently operate this lab. 3, 542 adult and pediatric procedures were conducted in 8 years, including coronary angiograms and percutaneous coronary interventions, device implantations, valvuloplasties, and cardiac defect closures, among others. There was a consistent expansion of the spectrum of procedures conducted in this cath lab each year. The initial lack of technical expertise and sourcing for equipment, as well as the continual need for sundries present(ed) major roadblocks. Government support and leveraging existing multi-level collaborations has provided a platform for several solutions. Sustainability of cath lab services remains a significant challenge especially in relation to the high cost of sundries and other consumables amidst a limited budget. Conclusion: A practical example of how centers in LMIC can set up and sustain a public cardiac catheterization laboratory is presented. Government support, research, and training collaborations, if present, become invaluable leverage opportunities.